2008
DOI: 10.1021/ma801187q
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Pressure on Boron Cross-Linked Polymer Gels

Abstract: Using steady-shear rheometry in combination with high-pressure 11B nuclear magnetic resonance spectroscopy (11B NMR), we have found that gels formed from water-soluble polymers containing vicinal hydroxyl groups cross-linked with various boron-containing compounds undergo significant structural changes that result in a pronounced loss of viscosity when placed under pressure. Importantly, gels from other cross-linking agents tested, including Ti(IV) and Zr(IV), did not show this loss in viscosity. The experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 19 publications
0
30
0
Order By: Relevance
“…Their applications have mainly been in very high temperature reservoirs where borate crosslinked fluids are no longer effective. 20 Parris et al 25 reported pressure dependency of guar crosslinked gels using different sources of borate ions. This viscosity reduction due to pressure was reversible.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Their applications have mainly been in very high temperature reservoirs where borate crosslinked fluids are no longer effective. 20 Parris et al 25 reported pressure dependency of guar crosslinked gels using different sources of borate ions. This viscosity reduction due to pressure was reversible.…”
Section: Reviewmentioning
confidence: 99%
“…Parris et al reported pressure dependency of guar crosslinked gels using different sources of borate ions. This viscosity reduction due to pressure was reversible.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that viscosity of borate crosslinked guar is a strong function of pressure and viscosity decreases with increasing the pressure. [98] Studying the rheological properties of PEC nanoparticles under typical pressure applied during a fracturing job or after the injection is recommended. This may give some insight about the shear sensitivity of EL2X-loaded nanoparticles mixed with HPG gel while they showed little shear sensitivity when mixed with HPG solution.…”
Section: Rheology Testsmentioning
confidence: 99%
“…Note that during the shear history testing, the fluid outlet is open to atmospheric pressure and does not have application of back pressure. Recent papers have noted a potential negative impact of high pressure on borate crosslinked fluid rheology (Parris et al 2008 andEngland et al 2011); it is not known to date whether shear profile in combination with high pressure imparts an additional affect on fluid performance. The shear rates, exposure times and temperatures for these tests were taken from the anticipated field conditions for both spotting and fracturing rates and are shown in Figure 2 for Field 1 and Figure 3 for Field 2.…”
Section: Shear History and Rheology Testsmentioning
confidence: 99%